Organic matter distribution and fluxes within a holm oak (Quercus ilex L.) stand in the Etna volcano - LEONARDI, S; Rapp, M; DENES, A (Plant Ecology, 1992)
Located at 1100 m above sea level, on the western site of the Etna volcano, the ecophysiology of the Mount Minardo holm oak coppice has been investigated for more then twenty years. In this stand, now 31 years old, the above ground biomass amounts to 15000 g m 2 of organic material, including leaves and perennial woody material. During these 31 years, the mean annual production has been around 775 g m 2. The yearly mean litterfall amounts to 310 g m 2, including 200 g m -2 of leaves, mostly two years old. The soil surface is covered by a litter layer amounting to 3150 g m-2. Each year, following Jenny's decomposition rate and field measurements, 290 g m- 2 of the litter turns into CO2, or becomes incorporated in the soil organic matter.
Keywords: Mediterranean forests; organic matter cycling; Quercus ilex L

L'impact du déboisement sur l'azote minéral susceptible d'être absorbé par un taillis de chêne vert (Quercus ilex L) en reconstitution - Merzouki, A; Lossaint, P; Billes, G; Rapp, M (Ann. For. Sci., 1990)
The impact of deforestation on the mineral nitrogen available during restoration of the holm oak (Quercus ilex L) coppice. The impact of deforestation on the biological activity of a mediterranean red soil was studied from January 1984 to April 1986 within a holm oak (Quercus ilex L) stand after clearcut. Part of the study involved the estimation of the amount of nitrogen available for vegetation both in the mature holm oak coppice and in the 1-2-yr-old recovery stand. The study indicates that the new shoots essentially took up nitrate nitrogen; however, the mature site used both nitrate and ammonium nitrogen as nitrogen source. The availability of mineral nitrogen, essentially nitrate, ranged from 47.4 to 118.6 kg·ha -1·yr-1 in the rebuilding site and 25.6 to 63.9 kg·ha-1·yr-1 in the mature stand. At the control site, ammonium nitrogen represented 43% of the total nitrogen available.
Keywords: Deforestation; holm oak coppice; nitrate; nitrogen availability; Quercus ilex L; shoots